Research assistants’ experiences of co-creating partnership learning communities for learning and teaching in higher education - Sterenberg, Gladys; O'Connor, Kevin; Donnelly, Ashlyn; Drader, Ranee (International Journal for Students as Partners, 2018)
Calls for enhancing student engagement in higher education have offered strong arguments for student-faculty partnerships in teaching and learning. Drawing on a conceptual model of partnership learning communities (PLC), we investigate the experiences of two undergraduate research assistants (co-authors of this paper) who participated in a PLC within a Scholarship of Teaching and Learning research study. In this paper, we use data from transcripts of four research conversations occurring over a three-year period. Evidence of research assistants’ experiences was co-analyzed using benefits and challenges identified in the literature. Our findings reveal that our PLC helped these research assistants develop student agency and provided opportunities for reflection on learning. We conclude that participating in our PLC helped the two research assistants develop deeper pedagogical relationships amongst themselves and with the faculty partners. Moreover, our study directly contributed to the development of our bachelor of education degree program while ensuring students were partners in that process.